The incidence of acute rheumatic fever and chronic rheumatic heart disease in the Russian population (2011–2012) - Rimma Mikhailovna Balabanova (Современная ревматология)
The problems of acute rheumatic fever (ARF) and chronic rheumatic heart disease (CRHD) are discussed. Carditis, polyarthritis, erythema annulare, subcutaneous nodules, and chorea minor are the main clinical manifestations of ARF caused by β-hemolytic streptococcus A. Cardiac failures emerge in 60–65% of patients after the first ARF episode. Repeated ARF attacks promote CRHD. The aim of the study is to evaluate the prevalence of rheumatic heart disease in different age groups in the regions of Russian Federation in 2011–2012. Materials and Methods. Analysis of the Ministry of Healthcare of the Russian Federation reports on population morbidity in 2011–2012 (Form N12).Results. The highest ARF prevalence was observed in 15–17-year-old teenagers, while the lowest, in adults over 18-year-old. The lowest CRHD figures were registered in juniors, while the highest ones, in adults. No ARF cases in 0–14-year-old children were registered in 31 entities of the Russian Federation; single cases, in 17 entities; no ARF cases in 15–17-year-old teenagers was registered in 37 entities, and 1–2 ARF cases were registered in 23 entities. Only in 10 entities, no ARF cases were registered in adults, and single cases were registered in 22 entities. Extremely unfavorable situations were found in the Chechen Republic (140 ARF cases in 0–14-year-old children) and in the Dagestan Republic (140 cases). High morbidity among 15–17-year-old teenagers was registered in tje Kaliningrad region (83 cases) and the Chechen Republic (100). ARF cases in adults were most frequent in St. Petersburg (124 cases), the Chechen Republic (154), and the Moscow region (161).The article lists the ARF and CRHD preventive measures.